Pengaruh Intensitas Penggunaan Gadget Terhadap Motivasi Belajar Siswa Sekolah Dasar - Nuryati, Nuryati; Harsono, Harsono; Wulandari, Murfiah Dewi; Rahmawati, Laili Etika; Widyasari, Choiriyah (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the influence of gadget usage intensity on the learning motivation of elementary school students. The background of this research stems from concerns over the increasing use of gadgets among children, which may potentially decrease their focus and enthusiasm for learning. This study employs a quantitative approach with a correlational design to examine the relationship between gadget usage intensity as the independent variable and learning motivation as the dependent variable. The research subjects consisted of fifth and sixth-grade students from several private elementary schools under the Dabin Yos Sudarso cluster, selected through purposive sampling. Data were collected using a Likert scale questionnaire covering frequency and duration of gadget use, as well as learning motivation indicators based on Uno’s theory. The instrument was tested for validity and reliability. Data analysis was conducted using Pearson Product Moment correlation with the help of SPSS version 26. The results show a significant influence between gadget usage intensity and learning motivation, with a regression coefficient value of 0.675 and a significance level of 0.000 (< 0.05). The higher the intensity of gadget use—especially for entertainment and social media—the lower the students’ learning motivation. Learning activities through gadgets tend to be minimal and are unable to compensate for the distractions from non-educational content. The findings highlight the importance of supervision and guidance from parents and teachers in directing gadget usage appropriately, so that technology serves as a learning support rather than a hindrance.